Single-Use Instrumentation, Cutting Blocks, and Trials Decrease Contamination during Total Knee Arthroplasty: A Prospective Comparison of Navigated and Nonnavigated Cases - Mont, Michael A.; Johnson, Aaron J.; Issa, Kimona; Pivec, Robert; Blasser, Kurt E.; McQueen, David; Puri, Lalit; Dethmers, Daniel A.; Miller, David W.; Ireland, Philip H.; Shurman, John R.; Bonutti, Petter (The Journal of Knee Surgery, 2013)
The purpose of this prospective controlled trial was to determine whether decrease in contamination could be achieved in nonnavigated and navigated total knee arthroplasties by replacing traditional saws, cutting blocks, and trials with specialized saws and single-use cutting blocks and trials. Various tray wrapping metrics during total knee arthroplasty were measured in 400 procedures performed by 8 different surgeons at 6 institutions. Instrumentation contamination was determined by counting the number of tray sterility indicators, pans, and instruments that were compromised. The results show that a decrease in contamination was evident in 57% (nonnavigated) and 32% (navigated) fewer compromises of tray sterility indicators, pans, and instruments. Single-use instruments show promising benefits, but further study is needed to confirm safety and efficacy before they can be widely adopted. The authors believe that the use of single-use instruments, cutting guides, and trial implants for total knee arthroplasty will play an increasing role in decreasing operating room contamination and potential deep infections.
Keywords: total knee arthroplasty; single-use instruments; cutting block; contamination; time saving